Early onset of postnatal individual vocal recognition in a highly colonial mammal species. Issue 1988 (7th December 2022) - Martin, Mathilde; Gridley, Tess; Elwen, Simon; Charrier, Isabelle
Abstract : Mother–young vocal recognition is widespread in mammals. The features of vocal recognition are known to be shaped by the ecological constraints faced by each species. In some species, a rapid establishment of mother–young vocal recognition is crucial for offspring's survival. However, knowledge of the precise features of this recognition system, especially the timing of the onset in the first hours after birth, is often lacking. Here we show that Cape fur seal females can recognize their pup's voice 2–4 h after parturition and that pups develop this aptitude 4–6 h after birth. This study is the first to investigate this mechanism in a wild and free-ranging mammal from only 2 h after birth. We report the fastest establishment of mother–young vocal recognition for any mammalian species, including humans, described to date. Such early vocal identification in pups suggests an in utero vocal imprinting. These findings highlight the synergistic role of environmental constraints and biological traits in optimizing the timing of individual vocal recognition onset in vertebrates.